(untitled) (American Journal of Business Management, Economics and Banking, 2023)
The article is devoted to the analysis of studies by foreign scholars regarding the theory of financial investigation, in particular, the term “financial investigations”. The article discloses the international experience in the field of regulation of financial investigations and the use of this concept in national legislation.